Anti-adhesive barriers in clinical practice: personalized patient management - Mekan R. Orazov; Viktor E. Radzinsky; Marina B. Khamoshina; Liudmila M. Mikhaleva; Sevinc Ya. Ismailzade (IP Berlin A.V., 2021)
The adhesive process is an urgent problem of operative gynecology. The number of women suffering from complications of the adhesive process is growing every year, not to mention the deaths associated with this problem. Polygenic etiology, low efficiency of treatment of the adhesion process determined the priority of searching for methods to prevent the process of adhesion formation or, at least, to reduce the severity of postoperative adhesion, at least a decrease in the severity of postoperative adhesion. The review presents the current paradigm of the pathogenesis of the formation of postoperative adhesions and the possibility of preventing adhesive disorders in gynecological patients.